Bitesized Teaching: educational futures for mental health training. (2nd January 2021) - Thompson, Sam; Bartram, Robert; Sweeney, Tom; Dias, Ryan; Scaife, Clair; Nicholls, Thomas; Reid-Roberts, Joanne; Reeve, Claire
Abstract : Background/Aims: Bitesized Teaching is an initiative that has worked successfully in Yorkshire and Derbyshire Mental Health Services for the last 5 years. It traditionally involves the delivery of high-impact, 10-minute tutorials on physical health topics, which take place once a week in the ward lunchtime handover period. This study evaluates an extension to the Bitesized Teaching scheme that incorporates delivering mental health-focused teaching topics to clinical staff on medical wards. Methods: Bitesized Teaching was delivered by a mental health liaison team to medical ward staff with three rolling sessions in an hour. To monitor the improvement in knowledge, a pre and post 1–5 Likert scale questionnaire was used. Results: The data showed that the knowledge from nursing staff improved on every topic. The topics 'psychosis' and 'talking to people with psychosis' had the greatest level of improvement in knowledge. Although the data reported a trend of increased knowledge, further analysis would need to explore the relevance the teaching topics had on clinical practice. Conclusions: The results outline the need for general and paediatric nursing staff to receive specific mental health training with the intention to improve treatment outcome and wellbeing to patients admitted to hospital for acute medical care.